Poly (ε-caprolactone) scaffolds functionalized by grafting NGF and GRGD promote growth and differentiation of PC12 cells - Chung, Tze-Wen; Lai, Dar-Ming; Chen, Shin-Der; Lin, Ya-I (Journal of biomedical materials research. Part A, 2014)
Poly(ε‐caprolactone) (PCL) scaffolds functionalized by grafting nerve growth factor (NGF) and Asp‐Arg‐Gly‐Asp (GRGD)(PCL‐NGF/GRGD) for neural tissue engineering. The influences of PCL‐NGF/GRGD scaffolds on the growth and differentiation of PC12 cells were investigated. The successfully grafting NGF and GRGD into PCL‐CS scaffold were verified by FTIR spectra. The densities of GRGD and NGF in the scaffolds were about 2.10×10−1 μmol/cm2 and 1.51×10−3 nmol/cm2. Growths of PC12 cells in PCL‐GRGD and PCL/NGF‐GRGD scaffolds via MTS measurements were significantly higher (p < 0.01, n = 4) than that in PCL‐CS or PCL‐NGF ones for three days of cultivation that was consistent with SEM observations. Moreover, the differentiation of PC12 cells, induced by NGF at 50 ng/mL for four days, in PCL‐NGF/GRGD scaffolds were qualitatively more numbers and longer outgrowth of neurites than those in PCL‐CS, PCL‐GRGD, and PCL‐NGF ones by SEM observations. The synergistic effects of grafting both NGF and GRGD ligands to PCL‐CS scaffolds on the growth and differentiation of PC12 cells provide a new biomaterial for neural tissue engineering. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 315–323, 2014.